The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.17650/1818-8346-2022-17-1-65-74
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic features of cutaneous T-cell lymphomas development on example of mycosis fungoides and Sezary syndrome

Abstract: Cutaneous T-cell lymphomas are a heterogeneous group of T-cell lymphoproliferative diseases affecting the skin. Mycosis fungoides and Sezary syndrome are the most studied variants of them. The literature review includes the latest published data on the pathological processes development in mycosis fungoides and Sezary syndrome and the diagnosis of these diseases. The genomic instability features in cutaneous T-cell lymphomas are described, the existing hypotheses of the origin of these diseases are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Genetic alternation in these receptors invariably affects TCR-mediated signaling, TCR complex assembly formation, and the level of various proteins such as TCR-associated enzymes, along with various transcription factors. All these are important for the proper execution of downstream signaling mediated through these receptors ( 8 , 26 , 26 , 38 , 50 , 76 , 83 , 96 , 97 ). It has been found that enhanced TCR activation through gain-of-function mutation in the extracellular domain of CD28 and the translocation of CTLA4-CD28 occurred in CTCL ( 98 , 99 ).…”
Section: Tumor Microenvironment Of T-cell Lymphoma and The Role Of Cy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic alternation in these receptors invariably affects TCR-mediated signaling, TCR complex assembly formation, and the level of various proteins such as TCR-associated enzymes, along with various transcription factors. All these are important for the proper execution of downstream signaling mediated through these receptors ( 8 , 26 , 26 , 38 , 50 , 76 , 83 , 96 , 97 ). It has been found that enhanced TCR activation through gain-of-function mutation in the extracellular domain of CD28 and the translocation of CTLA4-CD28 occurred in CTCL ( 98 , 99 ).…”
Section: Tumor Microenvironment Of T-cell Lymphoma and The Role Of Cy...mentioning
confidence: 99%
“…The overexpression of downstream signaling components like MAPK of cytokine receptors is due to gain-of-function mutation in B-Raf (p. Asp594Asn) and ERK-1 (p. Glu322Ala, p. Glu322lys) in MF subjects (74). In stage IV subjects of MF, mutations were identified in KRAS (Kristen Rat Sarcoma Viral oncogene homolog) and NRAS (Neuroblastoma RAS Viral oncogene homolog) genes (74)(75)(76). Immunohistochemistry studies revealed that in the nucleus of 53% cells of MF lesion, ERK1/2 gets phosphorylated, which has been associated with phospho-4E-BP1 (Eukaryotic Translation Initiation Factor 4E Binding Protein 1) (p-4E-BP1) upregulation.…”
Section: Cytokine and Cell Signaling In The Tumor Microenvironment Of...mentioning
confidence: 99%